A Comparison of the Concept of Waiting in Selected Quranic Verses and Excerpts of Marlow’s Dr. Faustus - Salwa Abdulamir Hadi; Saad Laftah Shamkhi; Basim Jubair Kadhim (Randwick International of Social Science Journal, 2023)
This research paper examines the concept of waiting as depicted in selected Quranic verses and in Marlow's play Dr. Faustus. Both sources explore the theme of waiting, but they present it from different perspectives and with different implications. The Quranic verses emphasize waiting as an act of surrender to divine timing, patience, and faith in Allah's plan. It is seen as a virtue that leads to spiritual growth and rewards in the afterlife. In contrast, Dr. Faustus portrays waiting as driven by human ambition and a desire for power and knowledge. The protagonist's impatience and misuse of power ultimately lead to tragic consequences. The differing portrayals of waiting highlight the contrasting roles of patience, faith, and ambition in the human experience. The paper delves into these differences and explores the broader philosophical and moral implications raised by each perspective. Ultimately, it prompts readers to reflect on how these concepts shape their lives and choices.